Time-dependent analysis of B0 → K0Sπ−π+γ decays and studies of the K+π−π+ system in B+ → K+π−π+γ decays - Amo Sanchez, Pablo del; Adametz, Aleksandra; Uwer, Ulrich; Bünger, Chris; Dittrich, Sebastian; Grünberg, Oliver; Heß, Miriam; Leddig, Torsten; Voß, Christian; Waldi, Roland (Physical review, 2016)
We measure the time-dependent CP asymmetry in the radiative-penguin decay B0→K0Sπ−π+γ, using a sample of 471×106 Υ(4S)→B¯B events recorded with the BABAR detector at the PEP-II e+e− storage ring at SLAC. Using events with mKππ<1.8 GeV/c2, we measure the branching fractions of B+→K+π−π+γ and B0→K0π−π+γ, the branching fractions of the kaonic resonances decaying to K+π−π+, as well as the overall branching fractions of the B+→ρ0K+γ, B+→K*0π+γ and S-wave B+→(Kπ)*00π+γ components. For events from the ρ mass band, we measure the CP-violating parameters SK0Sπ+π−γ=0.14±0.25±0.03 and CK0Sπ+π−γ=−0.39±0.20+0.03−0.02, where the first uncertainties are statistical and the second are systematic. We extract from this measurement the time-dependent CP asymmetry related to the CP eigenstate ρ0K0S and obtain SK0Sργ=−0.18±0.32+0.06−0.05, which provides information on the photon polarization in the underlying b→sγ transition.
Im Titel sind die Zeichen +, - und 0 hochgestellt und das S erscheint tiefgestellt
Gesehen am 08.05.2020